#### Question

# Factor. x^2 - 4x + 4?

Factor. x^2 - 4x + 4?

#### Answers

(x-2)2

x = 2

(x-2)(x-2)=(x-2)^2

(x-2)(x-2)

(x-2) (x-2)

( x - 2 ) ( x - 2 ) = ( x - 2 ) 2

Factor. x^2 - 4x + 4?

=> x2 - 2x - 2x + 4

=> x ( x-2) -2(x-2)

take (x-2) common

=> (x-2)(x-2)

Answer

x^2 - 4x +4

The easiest way to do this is to look at the -4x and the 4

When you set up the problem it looks like this :

(x ) (x )

the two empty spaces when added has to equal -4 and when multiplied it must equal 4 so from this we can figure out that the two numbers are going to be negative so:

(x - ) (x - )

now all thats left is to find the actual numbers which is 2

(x - 2) (x - 2)

We can check by F.O.I.L (first outer inner last) x times x is x^2, x times -2 is -2x, -2 times x is -2x, and -2 times -2 is + 4. so:

x^2 -4 +4

And now you have your answer =3 Hope I helped ^_^